Bad youth: juvenile delinquency and the politics of everyday life in modern Japan - Ambaras, David Richard (Studies of the Weatherhead East Asian Institute, Columbia University, 2006)
Introduction -- Unruly youth and the early modern polity -- Assimilating the lower classes -- Civilizing "degenerate students" -- Popularizing protection -- Preparing modern workers, policing modern play -- Juvenile delinquency and the national defense state -- Epilogue: The century of juvenile protection